E-LEARNING BASED IN ARABIC LANGUAGE COURSE IN HIGHER EDUCATION: POLICY AND IMPLEMENTATION STUDIES - Nasution, Sahkholid; Darussalam, Muhammad; Asari, Hasan; Al-Rasyid, Harun (JURNAL TARBIYAH, 2023)
Regulatively, Universitas Islam Negeri Sumatera Utara Medan already has a number of policies related to the use of E-Learning in this university. However, the number of E-Learning classes on the E-Learning page of Universitas Islam Negeri Sumatera Utara Medan is not directly proportional to the number of lecturers and courses, including Arabic language courses in the Arabic Language Education study programme at the Faculty of Tarbiyah and Keguruan Sciences. The purpose of this study is to describe the policy of using E-Learning and its implementation in learning Arabic sciences in the Arabic Language Education study programme at the State Islamic University of North Sumatra Medan. The research approach used is qualitative with descriptive method. Data was collected using literature study, documentation, and observation. The research data analysis was carried out in three stages, namely: Data Reduction, Data Presentation, and Conclusion Drawing. Data reduction is selecting e-learning policy documents and course classes available at UIN SU Medan e-learning based on Arabic language sciences courses, so that very important, less important, and unimportant data are clustered. The data is presented in the findings and discussion related to the e-learning policy and its implementation on the UIN SU Medan e-learning page. Conclusions are drawn inductively related to the completeness of e-learning policy documents and the availability of e-learning classes in Arabic language sciences courses on the UIN SU Medan e-learning page. The results of the study show that: (1). There is a policy on the use of E-Learning at the State Islamic University of North Sumatra Medan, in the form of Rector's Decree, Rector's Circular Letter and Guidebook (2). The policy has been implemented by a number of lecturers of Arabic Language Education Study Programme, it is proven that there are a number of E-Learning classes in Arabic language courses on the UIN SU Medan E-Learning page, although the quantity is still very low, only reaching 40%. Research findings show that the use of E-Learning at UIN SU Medan is not intended to replace face-to-face lectures in the learning process, but as an additional medium to realise effective and efficient learning.